2021
DOI: 10.1053/j.jvca.2020.10.041
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiology Practice During COVID-19 Pandemic: A New York Tertiary Hospital Experience

Abstract: As hospitals became overwhelmed during the Covid-19 pandemic in March-May in New York, Cardiology and Electrophysiology (EP) departments rapidly developed protocols for case selection as well modifying the practice of managing the cases. This process involved applying the American Heart Association (AHA) and Heart Rhythm Society (HRS) Guidelines for triaging the cases based on acuity, postponing the elective cases and modifying the way Cardiac Implantable Electronic Devices (CIEDs) interrogation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Of these, 45 studies were excluded based on the inclusion criteria. A total of 23 studies qualified for the final qualitative analysis 4 , 10 – 31 . A total of 4 studies were from the United States of America, 14 from Europe, and 1 from Pakistan, Oman, Iran, Japan, and New Zealand.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of these, 45 studies were excluded based on the inclusion criteria. A total of 23 studies qualified for the final qualitative analysis 4 , 10 – 31 . A total of 4 studies were from the United States of America, 14 from Europe, and 1 from Pakistan, Oman, Iran, Japan, and New Zealand.…”
Section: Resultsmentioning
confidence: 99%
“…The most common reason stated for the observed decline in EP procedures was the cancellation and postponement of nonurgent elective cases in the hospitals (15/23 studies, 65.2%). Seven (30.4%) studies reported their hospitals/centers being converted into COVID-19 referral centers 4 , 10 , 14 16 , 18 , 19 . Six (26.1%) studies reported an inverse relationship between rising COVID-19 cases and the declining rates of EP procedures 11 , 17 20 , 27 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations